Professional identity transitions, violations and reconciliations among new nurses in low- and middle-income countries - Mbuthia, DW; McGivern, G; English, M; Brownie, S; Jackson, D; Gathara, D; Nzinga, J (Elsevier, 2021)
We examine how new nurses construct their professional identity in Low- and Middle-Income Countries (LMICs) when they enter clinical practice and encounter practical norms violating procedural standards. We conducted interviews and focus group discussions with 47 Kenyan nurses. We describe new nurses experiencing ‘shock’ entering nursing practice (working and learning alone while responsible for many patients and doing ‘dirty work’), which contrasted with their idealized image and expectations of nursing and prior training. We explain this transition using theory about identity and identity work, which we argue elucidates nurses' experiences in LMICs. We suggest that nurses' transition into clinical practice violated pre-existing expectations for their professional identities, which then triggered identity work of ‘toughening up’, ‘maturing through experience’, and ‘learning practical norms’. Through this identity work, and finally experiencing satisfaction from caring for and nursing patients back to health, some nurses were able to restore their valued professional identity. Our findings highlight the need for professional educators and healthcare policymakers in LMICs to reconsider the way new healthcare workers are prepared for and socialized into professional practice, acknowledging that nursing practice is often very different to training. We argue for developing formative spaces in which health professionals can safely discuss practical norms deviating from procedural standards. Drawing on such conversations, practical norms benefitting the quality and safety in resource constrained contexts might then be incorporated into care standards and ways found to address practical norms harming of patient care.